Rancang Bangun Sistem Monitoring Suhu dan Kelembaban Tanah Berbasis Internet of Things - Ahmad Thoriq; Lukito Hasta Pratopo; Rizky Mulya Sampurno; Syauqi Hisyam Shafiyullah (PERTETA, 2022)
Soil temperature and humidity are important factors for plant growth. In the early and vegetative phases, plants require high humidity while in the late phase plants require low humidity. Soil temperature and humidity measuring instruments have been successfully made but are not yet connected to the internet network so that the sensor readings must be read directly on the LCD screen. This study aims to design an android-based soil temperature and humidity monitoring system. The monitoring system that was built is equipped with an SD Card as a backup of sensor reading data in case the internet is unstable. The method used in this research is engineering with the stages of literature study, analysis and design, hardware manufacturing, software development and system testing. The results show that there are 3 sensors, namely the DHT22 sensor, DS18B20 sensor, and the moisture sensor which are controlled by NodeMCU ESP32 with a battery power source of 3000 mAh 7.2 V which is step down to 5.0 V by LM2596. The system has a battery life of 10 hours 27 minutes, a soil temperature sensor accuracy of 98.05%, a soil moisture sensor accuracy of 90.2%, an air temperature accuracy of 98.3%, and an air humidity accuracy of 96.88%.